Biological characterization of African swine fever virus genotype II strains from north‐eastern Estonia in European wild boar. Issue 6 (24th January 2017) - Nurmoja, I.; Petrov, A.; Breidenstein, C.; Zani, L.; Forth, J. H.; Beer, M.; Kristian, M.; Viltrop, A.; Blome, S.
Summary: Due to its impact on animal health and pig industry, African swine fever (ASF) is regarded as one of the most important viral diseases of pigs. Following the ongoing epidemic in the Transcaucasian countries and the Russian Federation, African swine fever virus was introduced into the Estonian wild boar population in 2014. Epidemiological investigations suggested two different introductions into the southern and the north‐eastern part of Estonia. Interestingly, outbreak characteristics varied considerably between the affected regions. While high mortality and mainly virus‐positive animals were observed in the southern region, mortality was low in the north‐eastern area. In the latter, clinically healthy, antibody‐positive animals were found in the hunting bag and detection of virus was rare. Two hypotheses could explain the different behaviour in the north‐east: (i) the frequency of antibody detections combined with the low mortality is the tail of an older, so far undetected epidemic wave coming from the east, or (ii) the virus in this region is attenuated and leads to a less severe clinical outcome. To explore the possibility of virus attenuation, a re‐isolated ASFV strain from the north‐eastern Ida‐Viru region was biologically characterized in European wild boar. Oronasal inoculation led to an acute and severe disease course in all animals with typical pathomorphological lesions. However, one animal recovered completely and was subsequently commingled with three sentinels of the same age class to assess disease transmission. By the end of the trial at 96 days post‐initial inoculation, all animals were completely healthy and neither virus nor viral genomes were detected in the sentinels or the survivor. The survivor, however, showed high antibody levels. In conclusion, the ASFV strain from north‐eastern Estonia was still highly virulent but nevertheless, one animal recovered completely. Under the experimental conditions, no transmission occurred from the survivor to susceptible sentinel pigs.